2014
DOI: 10.1021/am504270c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multifunctional Magnetic NanoFlakes for Magnetic Resonance Imaging, Hyperthermia, and Targeting.

Abstract: Iron oxide nanoparticles (IOs) are intrinsically theranostic agents that could be used for magnetic resonance imaging (MRI) and local hyperthermia or tissue thermal ablation. Yet, effective hyperthermia and high MR contrast have not been demonstrated within the same nanoparticle configuration. Here, magnetic nanoconstructs are obtained by confining multiple, ∼ 20 nm nanocubes (NCs) within a deoxy-chitosan core. The resulting nanoconstructs—magnetic nanoflakes (MNFs)—exhibit a hydrodynamic diameter of 156 ± 3.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 48 publications
(91 reference statements)
0
43
0
Order By: Relevance
“…While we did not optimize relaxivities in this paper, Hyeon's group demonstrated that NCs can potentially provide transversal relaxivities r 2 , as high as 761 mM . 10 This result is about fivefold better than commercialized iron oxide nanospheres, Feridex, 10,13 indicating that NCs have potential advantages over nanospheres.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…While we did not optimize relaxivities in this paper, Hyeon's group demonstrated that NCs can potentially provide transversal relaxivities r 2 , as high as 761 mM . 10 This result is about fivefold better than commercialized iron oxide nanospheres, Feridex, 10,13 indicating that NCs have potential advantages over nanospheres.…”
Section: Introductionmentioning
confidence: 93%
“…13,33 The only limitation is that ferrimagnetic iron oxide NCs have size-dependent coercivity as the particle size increases while SPIOs are zero-coercive. 13,33 Therefore, when we engineer the iron oxide NCs with proper stabilizers, such as amphipathic polymers, it is possible to satisfy both high relaxivity and specific targeting. In this study, we demonstrated a good biodistribution of the nanoparticles (NPs) for bladder cancer imaging using 22 nm iron oxide NCs.…”
Section: Magneto-optical Properties Of Pmcnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles (MNPs) have gained a lot of attention in biomedical and industrial applications due to their biocompatibility, easy synthesis and ability of surface modification [18][19][20][21][22][23] . Moreover, they provide a large surface area for attachment of biorecognition elements and can then be easily separated from the liquid phase by a magnet, and spread immediately to zoom out which results highly appropriate in sensor and biosensor applications 16,17,22 .…”
Section: Introductionmentioning
confidence: 99%
“…[5]). Nevertheless, and apart from the occurrence of susceptibility artifacts at the tumor region via MRI that results from the use of high amounts of iron to obtain the appropriate local temperatures, MRI and magnetic hyperthermia are based on different and even counteracting parameters, which makes it challenging to combine them.…”
Section: Imaging Of Nanoparticle Depositions In Tumorsmentioning
confidence: 99%